Blaulichtgefährdung der Augen durch Lichtemittierende Dioden (LED)? - König, Yanyan; Huchzermeyer, Cord; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2020)
Background: In occupational and domestic environments people are increasingly exposed to artificial ligiit from light-emitting diodes (LEDs). LEDs flave peak emission in the blue range. In this review, we summarise the current knowledge of the possible effects of blue light exposure on ocular health. Effects of blue light on the regulation of physiological functions will be considered elsewhere. Methods: We performed a narrative review. We included preclinical data as well as epidemiological studies. We searched MEDLINE, Pubmed, the Cochrane Library and International Standard Randomised Controlled Trial Number (ISRCTN)-Register clinical trial registers from 01 January 2014 to 31 May 2019. Results: The accumulated experimental evidence obtained from different experimental models has indicated that excessive exposure to blue light can induce damage in the retinal pigment epithelium (RPE), in photoreceptors and ganglion cells. Previous epidemiological findings are equivocal regarding any causal links between blue light exposure and the development of macular degeneration (AMD). In vitro and in vivo evidence suggests that blue light exposure may influence the progression of uveal melanoma. Conclusions: Long-term effects of LEDs on ocular health cannot be definitively assessed on the basis of current knowledge. Susceptibility to blue light damage varies among the different species. The severity of light-induced retinal damage changes with the time of the day and depends on the diet and genetic background. Additional studies on the safety of long-term exposure to low levels of blue light are needed to determine the safety of LEDs for ocular health.
CRIS-Team Scopus Importer:2024-12-16
Keywords: blue light; light-emitting diode; macular degeneration; uveal melanoma